Skrbi za sebe – narcizam? Taking care of yourself - narcissism? - Nikić, Mijo (2021)
Autor najprije tumači i razlikuje pojmove autentične skrbi za se koja je prihvatljiva i pohvalna i narcizma, koji je patološka pojava. Obrazložena je tvrdnja da je malo onih koji istinski skrbe za se i koji odabiru najbolji put vlastitog ostvarenja. To je zbog toga što sebe dobro ne poznaju i što zanemaruju svoju duhovnu dimenziju, odnosno najjaču moć koju imaju, a to je moć samotranscendencije, kao i sposobnost da vjeruju, nadaju se i nesebično vole Boga i ljude. U nastavku članka autor iznosi tezu da narcis zapravo ne voli sebe. On u stvarnosti mrzi sebe, a zaljubljen je u oklop grandioznosti kojim se zaogrnuo da sakrije negativnu predodžbu sebe i veliki osjećaj manje vrijednosti i nemoći koji ga muči i progoni u podsvijesti. Na koncu autor donosi psihodinamiku narcističke ličnosti te daje smjernice integralne psihoterapije narcističkog poremećaja ličnosti.
The author first interprets and distinguishes the ideas of authentic self-care that is acceptable and praiseworthy and narcissism, which is a pathological phenomenon. It is argued that there are few who truly care for themselves and who choose the best path of their own realization. This is because they do not know themselves well and neglect their spiritual dimension, that is, the strongest power they have, and that is the power of self-transcendence, as well as the ability to believe, hope and selflessly love God and people. In the continuation of the article, the author presents the thesis that the narcissist does not really love himself. He actually hates himself, and he is in love with the armor of grandiosity with which he has wrapped himself to hide the negative image of himself and the great feeling of inferiority and powerlessness that torments and haunts him in the subconscious. Finally, the author brings the psychodynamics of narcissistic personality and gives guidelines for integral psychotherapy of narcissistic personality disorder.
Bibliografija
Summary.
Keywords: skrb za se; narcizam; duhovnost; psihologija; psihopatologija